Using Assistive Robotics for Aphasia Rehabilitation - Pereira, Jayr; Melo, Mariana; Franco, Natalia; Rodrigues, Francisco; Coelho, Alexsandro; Fidalgo, Robson (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Robots are widely used in motor rehabilitation of stroke victims. However, stroke can also leave cognitive sequelae that affect language, known as aphasia. In this context, this paper proposes the use of a humanoid robot as a mediator of a memory game, with the aim of helping in the recovery of language-related skills such as understanding of simple and complex orders; auditory memory; working memory; attention; understanding; perception; discrimination/differentiation; and general and specific motor coordination. This proposal was evaluated by speech therapists, based on the technology acceptance model (TAM), obtaining positive results, thus showing its great potential for acceptance.